Justice Energy as Formulation Equalization Electricity - Khairunnisah (PT Inovasi Pratama Internasional, 2023)
The management and use of energy, including electricity, in Indonesia addresses three aspects: energy security (ensuring national electricity demand and future sustainability) and energy equity, ie increases and decreases in availability/electrification levels). The electrification ratio should highlight the use of electricity beyond lighting and measure how far electricity boosts people's economies, energy activists say. At least 500,000 households in Indonesia did not have access to electricity until May 2021, according to government data. The majority of them live in remote or outermost villages. This paper will examine 2 (two) things that become problem formulation, namely, first, how is the concept of energy justice in terms of electricity in remote areas? and How is Energy Justice as a Concept of Electricity Equity. Rural electricity program policy aims to expand access to electricity in areas that have not been reached by electric power distribution networks in rural areas. Ecological justice is concerned with the distribution of the environment among various forms of life. Ecological justice is a theoretical approach derived from established environmental justice theory and practice. Environmental justice bases its principles on three main dimensions: distribution, recognition, and participation.